Contributions of Bioinformatics for computing education in the detection of programming assignment plagiarism - Gomes, Kaio P.; Matos, Simone N. (Anais do Simpósio Brasileiro de Informática na Educação (SBIE); 2019: Anais do XXX Simpósio Brasileiro de Informática na Educação, 2019)
Any source code can be modified in several ways to confuse plagiarism detection systems. Such diverse modifications require the usage of systems which can handle different types of plagiarism. The usage of automatic source code plagiarism detectors has implications for computing education. This paper extends Pedersen's work, a Bioinformatics method, by performing the application of this method on programming plagiarism domain, and by analyzing the usage of such tool through a discussion associated with the support for professors in assessing students' assignments. The application results are compared to a commonly used solution for the same purpose, the JPLAG tool. As a result of the evaluating study, the applied method showed a higher rate of similarity for specific types of plagiarism. Also, as a result of the analysis involving the use of an automatic tool for plagiarism in programming, showed the benefits for computing education.